MBARI mapping AUV operations in the gulf of California 2015 - Thompson, D.; Caress, D.; Thomas, H.; Conlin, D. (Oceans 2015 : MTS/IEEE Washington : 19-22 October 2015, 2015)
The Monterey Bay Aquarium Research Institute (MBARI) has conducted high-resolution multibeam bathymetry, sidescan, and subbottom sonar surveys in the Gulf of California and offshore northern Baja California using an autonomous underwater vehicle (AUV) as part of a fourmonth, two-ship oceanographic expedition, Fig 4. The seafloor mapping AUV D. Allan B was operated from R/V Rachel Carson, achieving 21 successful surveys during February and March 2015, operating to a maximum depth of 3800m. The 1meter lateral resolution bathymetry maps and subbottom profiles were used to guide subsequent ROV Doc Ricketts dives made from MBARI's R/V Western Flyer, which combined visual surveys, sampling, and in situ experimentation by several different science groups. The vehicle is a modularized Dorado Class 53 cm (21 inch) diameter, 6.4 meter (21 feet) length, 770 kg (1700 pounds) air weight. The interior of the AUV floods with water when launched; electronics are contained in either one-atmosphere hermetic housings or in pressure-compensated enclosures. The AUV is ballasted to be approximately 3.63 kg (8 pounds) positive in seawater. Flotation is accomplished with 6000 meter rated syntactic foam. The D. Allan B has three mapping sonar systems onboard: a Reson 7125 200 kHz multibeam sonar, an Edgtetech FS-AU Sonar Package which includes 110/410 kHz chirp sidescan and 1-6 kHz chirp subbottom profiler. The Mapping AUV has 10 kWhr of lithium-ion batteries achieving about 16 hours endurance at a speed of 1.5 meters per second, for a maximum range of about 85 km. The Mapping AUV is equipped with a Kearfott inertial navigation system (INS) with Doppler velocity log, a Paroscientific pressure sensor, and an ultrashort baseline (USBL) and acoustic modem for communications and navigation. It also has an Iridium Satellite Short Burst Data modem, a drop weight, radio direction finder, Homer Pro sonar beacon and visible strobe location aids for emergency relocation. Propulsion is accomplished with a duct-protected articulated propeller which provides 52 Newtons (12lbf) of thrust at 300 rpm as well as elevator and rudder functions. The turning diameter is less than 20 meters; climb/dive rate is between 30 and 60 meters per minute. Launches and recoveries were made from the R/V Rachel Carson, a 41.1 m (135 ft) length, 10.4m (34 ft) beam former oilfield supply boat that operates with six crew and six science personnel, Fig. 1, Fig 3. It is outfitted with an AK25 sea crane for AUV launch and recovery, as well as a PM43 main crane for overboarding a remotely operated vehicle (ROV). Once the AUV is in the water, the mission is sent from a computer on the Rachel Carson to the AUV over a wireless Freewave Ethernet link. At the start of the mission, the AUV spirals down to the start-of-line while receiving USBL-based position updates from the support vessel over the acoustic modem. Once on bottom, the support vessel is free to perform other operations. A Bottom Pressure Recorder used to provide in situ tide data for bathymetry correction was deployed prior to most of the AUV missions, and recovered afterwards, using an AVTRAK beacon to burn an anchor release wire. The seafloor mapping data were processed using the open source software package MB-System, developed at MBARI and the Lamont-Doherty Earth Observatory. Post-processing steps include interactive bathymetry editing and tide correction. Survey navigation is adjusted so that bathymetric features match in overlapping swaths, yielding navigation with relative precision equivalent to the 1-m bathymetric lateral resolution. Sidescan data are corrected for 3D grazing angles using the 1-m resolution bathymetry.